2021
DOI: 10.3389/fpsyt.2021.727687
|View full text |Cite|
|
Sign up to set email alerts
|

Risk of Bleeding Associated With Antidepressants: Impact of Causality Assessment and Competition Bias on Signal Detection

Abstract: Introduction: Until now, methods of pharmacovigilance as disproportionality analysis were not capable of proving the otherwise well-established increased bleeding risk related to antidepressants (ADs). As bleeding events with ADs often occur in combination with antithrombotics, they might not be considered causative of, but merely “linked” with, the bleeding event. Therefore, we hypothesized that the causality assessment of bleeding events in association with ADs and the competitive impact of antithrombotics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…Possible mechanisms underlying those interactions include the addition of side effects. Studies showed that Eleutherococcus senticosus contains dihydroxybenzoic acid, which has antiplatelet activity (Yun-choi et al, 1987;Friedman et al, 2007) and may increase the risk of hemorrhage associated with the use of SSRIs and SNRIs (Zeiss et al, 2021). There is only one study reporting adverse bleeding-related events associated with the use of this adaptogen.…”
Section: Discussionmentioning
confidence: 99%
“…Possible mechanisms underlying those interactions include the addition of side effects. Studies showed that Eleutherococcus senticosus contains dihydroxybenzoic acid, which has antiplatelet activity (Yun-choi et al, 1987;Friedman et al, 2007) and may increase the risk of hemorrhage associated with the use of SSRIs and SNRIs (Zeiss et al, 2021). There is only one study reporting adverse bleeding-related events associated with the use of this adaptogen.…”
Section: Discussionmentioning
confidence: 99%
“…Once the GP has putatively diagnosed depression, the target outcome should be to obtain functional remission [60] [61], and to achieve complete psychosocial recovery of the patient [62]. According to the most recent scientific evidence, the cornerstone strategy for reaching clinical effectiveness is a personalized ("tailored") treatment based on a decision tree [63], which should primarily include the patient in the choice of medication(s), addressing potential therapeutic effects, likely time to respond, general tolerability, and possible adverse effects (e.g., weight gain, sexual adverse events, cardiovascular adverse events) [64]. Trazodone is often selected as a first choice antidepressant in primary care settings due to its multimodal action (anxiolytic, hypnotic, antidepressant) exerted at different dosages, as well as to its wide range of available formulations, its rapid efficacy, a low rate of adverse events, and less interaction with other drugs, all of which make trazodone extremely useful and malleable in high comorbid patients [71] [72] [73].…”
Section: Standing On the Frontline: The Unmet Needs Of Depression In ...mentioning
confidence: 99%
“…Once the GP has supposedly diagnosed depression, the target outcome should be to obtain functional remission ( 59 , 60 ) and to achieve complete psychosocial recovery of the patient ( 61 ). According to the most recent scientific evidence, the cornerstone strategy for reaching clinical effectiveness is a personalized (“tailored”) treatment based on a decision tree ( 62 ) which should primarily include the patient in the choice of medication(s), addressing potential therapeutic effects, likely time to respond, general tolerability and possible adverse effects (e.g., weight gain, sexual adverse events, cardiovascular adverse events) ( 63 ).…”
Section: A Close Look At the Frontline: The Unmet Needs Of Depression...mentioning
confidence: 99%